Predacious activity of Ants (Hymenoptera: Formicidae) in conventional and in No-till agriculture systems - Lange,Denise (2008)
This study had the objective of assessing the differences in foraging activity of the predacious ants between two areas, one conventional and other with no-till agriculture systems. The research was conducted in two contiguous 1.5 ha plots in Dourados MS, Brazil, from February 2001 to December 2003. Each plot received 750 baits (Nasutitermes termites), 425 at daylight and 325 at night. The termites were placed on the filter paper, on the ground, and ant attack was monitored for 15 min, until removed. Sixteen ant species were found in the no-till system and nine in the conventional system. Baits removed from no-till were significantly higher than the conventional plots and were influenced by the sampling time, at day or night. The seasons of the year did not significantly explain the variations in the structure of the predacious ant communities in neither of the systems. The significant differences at foraging activity and ant richness between the areas indicated that the no-tillage system could improve environmental quality of the cropping and therefore, became an important tool for the integrated pest management programs.